Sustainable Improvement of the Community Satisfaction Index in Dispendukcapil Semarang City: A Dual-Stage CFA-IPA Analysis: Peningkatan Indeks Kepuasan Masyarakat Berkelanjutan Di Dispendukcapil Kota Semarang: Pendekatan Dual-Stage CFA-IPA Analysis - Noviananda Puji Lestariningtyas; Teguh Hardi Raharjo (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to evaluate the IKM model and identify priorities for improving public services at the Semarang City Population and Civil Registration Office using quantitative methods. The analysis employed a CFA approach using AMOS as well as an IPA approach. The CFA results indicate that the IKM measurement model possesses good construct validity, where all indicators significantly contribute to the latent factor of public satisfaction. Meanwhile, the IPA analysis revealed that the overall service satisfaction level reached only 84.15%, meaning the services have not yet fully met public expectations. The results of the Cartesian diagram mapping revealed that the dimensions of system mechanisms and procedures, and completion time, are the top priorities for improvement. These findings recommend that the Semarang City Population and Civil Registration Office prioritize improvements in service procedures and completion time, with the aim of sustainably increasing public satisfaction.